(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The study aimed at assessing the in-store losses of rice caused by biotic and abiotic factors in the storage structures/containers at farmers level. The farmers suggested ways of reducing in-store losses of rice are also discussed. A total of 96 villages covering 26 Upazilas under 14 civil districts across all the divisions of the country were selected for present investigation. The districts were put under five different regions to capture the dimensions of study. In all, 1360 samples of Aus, Aman and Boro rice farmers were selected randomly and purposively from the study areas and put into marginal, small, medium and large farm category based on their land ownerships. Data were collected through pre-tested questionnaires. Different traditional rice storage structures/containers like Dole, Berh, Inside-house Gola, Outside-house Gola, Steel/Plastic drums, Motka, Gunny bag and Plastic/Polythene bags were commonly used by farmers in the study areas. The storage time of rice varied from 3.05 to 7.24 months irrespective of rice, farm and region with the overall average being 5.5 months. Significant losses in stored rice occurred through the activities of both biotic and abiotic factors. The average in-store losses occurred for Aus, Aman and Boro rice were respectively 3.68, 3.80 and 4.12% with the aggregated average being 3.92%. The average in-store losses of rice in large, medium, small and marginal farmers were 4.48, 3.92, 4.0 and 3.59% respectively. The in-store losses occurred in regions 1, 2, 3, 4 and 5 were 3.31, 5.23, 3.62, 4.44 and 3.25% respectively. The farmers suggested a number of ways for reducing in-store losses of rice including training on capacity building and awareness for safe storage, credit for constructing durable storage structure, construction of common storage structures at village/union level, preventive measures against biotic and abiotic factors, supplying farmers with durable storage containers and, keeping them well ahead informed about the natural calamities. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12105 J. Bangladesh Agril. Univ. 10(1): 133144, 2012